2023
DOI: 10.21037/jtd-22-1492
|View full text |Cite
|
Sign up to set email alerts
|

A smartphone-based application for cough counting in patients with acute asthma exacerbation

Abstract: Background While tools exist for objective cough counting in clinical studies, there is no available tool for objective cough measurement in clinical practice. An artificial intelligence (AI)-based cough count system was recently developed that quantifies cough sounds collected through a smartphone application. In this prospective study, this AI-based cough algorithm was applied among real-world patients with an acute exacerbation of asthma. Methods Patients with an acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Different machine learning (ML) and AI-based studies on chronic cough and asthma have been carried out in recent years, by leveraging the newest medical technologies [ 8 ]. An AI-based cough count, CoughyTM [ 9 ], system was recently developed that quantifies cough sounds collected through a smartphone application. Study results showed that suggest that CoughyTM could be a novel solution for objectively monitoring cough in a clinical setting.…”
Section: Related Workmentioning
confidence: 99%
“…Different machine learning (ML) and AI-based studies on chronic cough and asthma have been carried out in recent years, by leveraging the newest medical technologies [ 8 ]. An AI-based cough count, CoughyTM [ 9 ], system was recently developed that quantifies cough sounds collected through a smartphone application. Study results showed that suggest that CoughyTM could be a novel solution for objectively monitoring cough in a clinical setting.…”
Section: Related Workmentioning
confidence: 99%
“…Different machine learning (ML) and AI-based studies on chronic cough and asthma have been carried out in recent years, by leveraging the newest medical technologies [17]. An AI-based cough count, CoughyTM [14], system was recently developed that quantifies cough sounds collected through a smartphone application. Study results showed that suggest that CoughyTM could be a novel solution for objectively monitoring cough in a clinical setting.…”
Section: Related Workmentioning
confidence: 99%